ANALISIS PERMINTAAN KEDELAI DI INDONESIA - Septi Rostika Anjani; Dwidjono Hadi Darwanto; Jangkung Handoyo Mulyo (Universitas Sebelas Maret, 2015)
This study aims to analyze the factors that influence the demand of soybean in Indonesia. The research method uses descriptive analysis of secondary data which includes the price of imported soybeans, the price of chicken, per capita income, the rate of inflation and import tariff policy year period 1980-2013 which sourced from FAO and other sources. Estimation of demand function using multiple linear regression analysis were transformed in the form of natural logarithm. Regression analysis showed that soybean demand in Indonesia was influenced partially by prices of chicken, per capita income, and the rate of inflation. The price elasticity of demand of soybean in Indonesia is inelastic, that is equal 0,22. While the income elasticity of demand for soybeans is positive which means that soy is a staple item for the Indonesian people.